Gut microbiota: Implications in Parkinson's disease. (May 2017) - Parashar, Arun; Udayabanu, Malairaman
Abstract: Gut microbiota (GM) can influence various neurological outcomes, like cognition, learning, and memory. Commensal GM modulates brain development and behavior and has been implicated in several neurological disorders like Alzheimer's disease, multiple sclerosis, amyotrophic lateral sclerosis, anxiety, stress and much more. A recent study has shown that Parkinson's disease patients suffer from GM dysbiosis, but whether it is a cause or an effect is yet to be understood. In this review, we try to connect the dots between GM and PD pathology using direct and indirect evidence. Highlights: Possible connections between gut microbiota and Parkinson's pathology. Mediatory role of gut microbiota in neurological disorders. Gut microbiota, insights into mechanistic control over brain and behavior.